Netralisasi Limbah Cair Industri Tahu Menggunakan Metoda Elektrokoagulasi dengan Elektroda Al-Al dengan Variabel Waktu Proses dan Ketebalan Plat - Idral Amri; Ihda Nurjanah; Irdoni (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2020)
The tofu factory located in Pangkalan Kerinci, Pelalawan District, produces 1 m3 of liquid waste every day and are immediately disposed of without going throught the processing before release to environment. The analysis shows that the liquid waste is not in accordance with Permen LH No. 5 2014. This will deerease the oxygen level in the water. The purpose of this study was to determine reduce levels of TSS, BOD and pH with plate thicknes and prosesing time. Neutralization of liquid waste of tofu industry. The electrocoagulation method was used to reduce BOD, TSS and neutralize pH by varying the time, plate thickness. The conclusions obtained are: (1) Time variation (20, 40 and 60 minutes), and effective time is 60 minutes, current strength of 0.6 A decreases 72% BOD concentration, TSS 69.9% and pH becomes 6.01. (2) Variation in plate thickness (0.5; 1.0 and 1.5 mm), and effective plate thickness of 1 mm at 60 minutes can reduce BOD concentration 73.14%, TSS 68.78%, pH becomes 6.83. The results of the research obtained are in accordance with Permen LH No.5 of 2014.